Optimization of a robust sigmoid PID controller for automatic voltage regulation using the nonlinear sine-cosine algorithm with amplifier feedback dynamic weighted (AFDW) system - Ahmed, Islam; Mohd Helmi, Suid; Mohd Ashraf, Ahmad; Ahmad, Salmiah; Mohd Falfazli, Mat Jusof; Mohd Zaidi, Mohd Tumari (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
The given paper presents a robust Sigmoid-based Proportional-Integral-Derivative (SPID) controller for Automatic Voltage Regulator (AVR) systems, optimized using the Nonlinear Sine Cosine Algorithm (NSCA) enhanced with the Amplifier Feedback Dynamic Weighted (AFDW) system. Conventional PID controllers are frequently struggling with parameter variations and external interruptions that lead to instability and reduced performances in AVR systems. The proposed SPID controller overcomes these limitations by incorporating nonlinear sigmoid functions, improving the AVR system's robustness and dynamic response. While the AFDW system improves stability and responsiveness by dynamically adjusting the feedback weight, the NSCA balances exploration and exploitation to optimize controller parameters. The primary contribution of the present research is an overview of the NSCA-SPID controller, which offers superior results in voltage regulation compared to traditional PID and other metaheuristic-tuned controllers, enhancement in settling time, elimination of overshoot, and improvement in steady-state error. Additionally, performance index and statistical performances are used to validate the proposed SPID controller. Simulation results demonstrate significant achievements that emphasize the effectiveness of the NSCA-SPID controller toward enhancing the AVR system stability and controller design’s performance under varying load conditions. Finally, the proposed NSCA-SPID controller provides a promising solution for Enhancing the regulation of voltage in power systems, providing Superior and efficient technique for practical applications.